Wilms' Tumor—Lessons and Outcomes—A 25-Year Single Center UK Experience. (1st August 2014) - Fawkner-Corbett, David W.; Howell, Lisa; Pizer, Barry L.; Dominici, Carlo; McDowell, Heather P.; Losty, Paul D.
<x xml:space="preserve">Abstract</x> Wilms' tumor (WT) is a common childhood renal cancer. A 25-year single center UK experience is reported. During 1985–2010, 97 children underwent immediate nephrectomy or delayed resection of tumor after chemotherapy. Survival, morbidity, and late effects following treatment are described. Tumor distribution was: Stage I, 25.7% (n = 25); Stage II, 24.7% (n = 24); Stage III, 26.8% (n = 26); Stage IV, 17.5% (n = 17); and Stage V, 5.2% (n = 5). Immediate nephrectomy was performed in 39% (n = 38) patients with elective delayed resection in 61% (n = 59) cases. Ten patients had cavotomy to excise tumor involving vena cava territory. Two cases required cardiopulmonary bypass. Tumor rupture was recorded in eight (8.5%) total operated cases—after immediate (n = 5/37), 13.5% vs delayed nephrectomy—(n = 3/57), 5.2%; X2P = .154. From 2001 onwards, one case of tumor rupture was recorded at this center after the universal adoption of UKW3 and SIOP guidelines advocating preoperative chemotherapy and delayed nephrectomy for all WT. Three treatment-related deaths occurred—hepatic veno-occlusive disease (n = 2) with actinomycin D and a single WT fatality due to vascular injury. Overall survival was 84.5% (82/97 cases). Two patients developed "late malignancies" —thyroid cancer and a basal cell carcinoma. This study demonstrates excellent survival for WT comparable with national outcomes and international cooperative studies. Adverse events with chemotherapy and surgery, including "late onset, " second malignancies deserve special consideration.